LIFE-COURSE DETERMINANTS OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE: DO STATE CIGARETTE TAXES MATTER?. (11th November 2018) - Hua, C; Sun, N; Nguyen, M; Brown, S
Abstract: COPD is the fourth leading cause of death in the United States and is most common among adults aged 65 and over. There is a well-established relationship between a lifetime of cigarette smoking and COPD. However, no research has been identified that examines the relationship between cigarette tax and COPD prevalence rates. Furthermore, no literature has examined the influence of different tax rates within bordering counties on prevalence of COPD; this is problematic because the literature indicates that people travel to obtain the lowest priced cigarettes. Therefore, this research examines whether state cigarette tax rates are associated with COPD prevalence rates and whether counties close to states with low taxes have higher COPD rates. Small-area estimates of COPD at the county-level are obtained from the Centers for Disease Control; these estimates are calculated using the 2015 Behavioral Risk Factor Surveillance System data. Cigarette tax data come from the CDC State Tobacco Activities Tracking and Evaluation (STATE) system. Demographic data come from the 2011–2015 American Community Survey. Air quality data come from the United States Environmental Protection Agency. Regression analyses indicate that, after controlling for demographic characteristics and air quality, a $1.00 increase in cigarette tax is associated with a .25 percentage point decrease in COPD prevalence rate. Using GIS techniques, , further models calculate the average distance an individual within a county must travel to visit the closest lowest-price border state. Implications for policy are discussed.